Адміністративні проступки і кримінальні правопорушення - Буряк, Є. В.; Buriak, Ye. V.; Комзюк, А. В.; Komziuk, A. V.; Назаренко, П. Г.; Nazarenko, P. H.; Алена Комзюк (Академічні візії. - 2023. - Вип. 21., 2023)
Досліджено адміністративні проступки і кримінальні правопорушення, їхні види. Запропоновано комплексний аналіз розмежування адміністративного проступку й кримінального правопорушення, визначено їхні ознаки, наслідки та види відповідальності.

The purpose of the article is to investigate administrative and criminal offenses, to identify the most common types of these crimes, and to analyze the measures taken by law enforcement agencies to counter them. A comprehensive study of the topic was conducted, including an analysis of relevant legislation and case studies. The most common administrative and criminal offenses are caused by historical, social, political, and economic changes. Administrative law constantly changes and forms new relations between the state and society. The purpose of the article is administrative offenses and criminal offenses, their types, and their consequences. The concept of an administrative offense was recently introduced into Ukrainian legislation. The results of the study showed that administrative and criminal offenses are a problem in Ukraine and other countries. An administrative offense has less social harm than a criminal offense. Preventive measures such as raising public awareness of the consequences of crimes are important for reducing the number of such types of offenses. It is necessary to distinguish the concept of an administrative offense and a criminal offense. Criminal and administrative offenses pose a threat to the stability and development of modern society. They call for greater attention and resources to be directed at preventing and combating such crimes. Administrative offenses and criminal offenses differ from each other. The article proposes normative legal acts that interpret responsibility for administrative offenses and criminal offenses. The article proposes modern administrative‐ legal regulation on issues of administrative offenses and criminal offenses. In conclusion, the article may be useful for legal specialists, teachers, and students who study administrative and criminal offenses in more detail.

Исследованы административные проступки и уголовные правонарушения, их виды. Предложен комплексный анализ разграничения административного проступка и уголовного правонарушения, определены их признаки, последствия и виды ответственности.
Administrative offenses and criminal offenses
Keywords: адміністративний проступок; administrative offense; административный проступок; адміністративне правопорушення; administrative offence; административное правонарушение; кримінальне правопорушення; criminal offense; уголовное правонарушение; адміністративно‐правова кваліфікація; administrative-legal qualification; административно-правовая квалификация; суспільні відносини; public relations; общественные отношения